Strategies of maternal discipline in at-risk and not-at-risk groups - Coelho, Maria João (2011)
The present study aimed to characterize and compare two groups of mothers, the psychosocial risk group and the non-risk group, with respect to discipline strategies. Mothers who participated in the study had children between 12 and 48 months. It was used an observational methodology that consisted in filming the interaction of mothers with their children in two different tasks “clean up” and “don’t touch”. These tasks have been coded according to the Scales of Van der Mark, Van IJzendoorn and Bakermans-Kranenburg to positive and coercive discipline strategies (2002). The main results of this study point out a pattern: mothers of psychosocial risk group use more often coercive discipline strategies, while the group of mothers at non-risk condition use more frequently positive discipline strategies.